Negotiating Power and Identity in Female Leadership within Patriarchal Organizational Cultures - Suharti Suharti; Aliah Bagus Purwakania Hasan (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to examine how women leaders negotiate power and build professional identities in patriarchal organizational cultures. In particular, this study highlights the interaction between gender expectations, leadership practices, and organizational structures that often marginalize women's authority in managerial contexts. This study uses an interpretive qualitative approach with semi-structured interviews with 12 women leaders at various managerial levels in male-dominated organizations in Indonesia. Thematic analysis was used to uncover patterns of identity negotiation, resistance strategies, and adaptive leadership practices in patriarchal environments. The results show that women leaders face ongoing challenges such as gender stereotypes, double standards of competence, and symbolic exclusion from decision-making. However, they apply adaptive strategies such as relational leadership, strategic network building, and reconstructing femininity as a source of leadership legitimacy. This research also confirms that identity negotiation is a dynamic process influenced by organizational culture, peer recognition, and self-reflection. Women's leadership in patriarchal organizations is characterized by continuous negotiation between conformity and resistance. Although institutional structures reinforce gender hierarchies, women leaders demonstrate agency through tactical adaptations that allow them to maintain authority while encouraging inclusive leadership practices. This study is limited to the qualitative scope and cultural context of Indonesia, so the findings may not fully represent cross-cultural variations in women's leadership experiences in other patriarchal contexts. This study contributes to the literature on human resource management and gender studies by offering a contextual understanding of women's leadership strategies in patriarchal systems. In addition, this research provides practical insights for organizations to design gender-sensitive HR policies, leadership development programs, and organizational cultures that are more inclusive and empower women.